Competitive balance and spectator attendance: the case of the Korean Professional Baseball League. (2015) - Cha, Jae Hyuk; Chang, Kyungro; Kim, Taehee
This study aims to analyse whether the uncertainty of outcome hypothesis applies to the Korean Professional Baseball League (KPBL). Specifically, the purpose of this study is to examine the competitive balance of the KPBL and investigate socioeconomic factors that may influence attendance. A structural time-series model is estimated to investigate the relationship between competitive balance and average game attendance in the KPBL from 1982 to 2012. The results provide evidence that the uncertainty of outcome hypothesis, as measured by competitive balance, does apply to the KPBL.